2x^2+7x=-3
2x^2+7x+3=0
x^2+(7/2)x+(3/2)=0
x1=-3
x2=-(1/2)
or
a=2, b=7, c=3
x1=(-b+sqrt((b^2)-4ac))/2a
=(-7+5)/4
=-(1/2)
x2=(-b-sqrt((b^2)-4ac))/2a
=(-7-5)/4
=-3
2006-12-03 02:39:29
·
answer #1
·
answered by Xiangwei Xi 3
·
0⤊
0⤋
2x^2 + 7x = -3
becomes 2x^2 + 7x + 3 = 0 by adding +3 to both sides
using the quadratic formula
a = 2
b = 7
c = 3
2006-12-03 10:40:31
·
answer #2
·
answered by lots_of_laughs 6
·
0⤊
0⤋
a=2, b=7, c=3
Substitute the value in the quadratic formula.
x= -(1/2)
x= -3
2006-12-03 10:39:13
·
answer #3
·
answered by Nikko 2
·
0⤊
0⤋
get you equation in the form ax^2 + bx + c = 0
so 2x^2 +7x + 3 = 0
quadratic equation x = -b + or - sqr(b^2 -4ac)/2a
plugin variabls and solve for x twice
x= -7 + sqr(49 - 4(2)(3))/2(2)
x= -7 - sqr(49 - 4(2)(3))/2(2)
-4(3)(2) = -24, 2(2) = 4
x= -7 + sqr(49 - 24)/4
x= -7 - sqr(49 - 24)/4
49 - 24 = 25
x= -7 + sqr(25)/4
x= -7 - sqr(25)/4
sqr(25) = 5
x= -7 + 5/4
x= -7 - 5/4
5/4 = 1.25
x= -7 +1.25
x= -7 - 1.25
x = -5.75
x = -8.25
2006-12-03 11:41:40
·
answer #4
·
answered by ikeman32 6
·
0⤊
0⤋
2x^2+7x=-3
2x^2+7x+3=0
It's hard to explain so please go to
http://www.purplemath.com/modules/quadform.htm
now, u can see the formula to get the value of x rite... x=-b........ if you plug that in the equation it becomes
x=-7 +or-squarerootof(7^2-4(2*3)) and all that divided by 2(2)
2006-12-03 10:46:48
·
answer #5
·
answered by Jeff 2
·
0⤊
0⤋
x= (-7(+ or -)sqrt(49-24))/4
x=(-7(+or-)5)/4
x= -12/4 , -2/4
x= -3,-1/2
2006-12-03 10:39:07
·
answer #6
·
answered by Rajkiran 3
·
0⤊
0⤋